2018
DOI: 10.31234/osf.io/5387k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Birth Order on Intelligence, Educational Attainment, Personality, and Risk Aversion in an Indonesian Sample

Abstract: Few studies have examined birth order effects on personality in countries that are not Western, educated, industrialized, rich, and democratic (WEIRD), even though theories have generally suggested interculturally universal family dynamics as the mechanism behind birth order effects, and prominent theories such as resource dilution would even predict stronger effects in poorer countries. Here, we investigate a subset of up to 11,188 participants of the Indonesian Family Life Survey, an ongoing representative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Using specification curve analysis (16,17), an exhaustive econometric approach, they observed, in contrast to previous findings on the selection of sports and risky play, that birth order had no substantive effect on risk taking, or indeed on the various personality dimensions examined. Recently, these results were supported in an Indonesian sample (9).…”
Section: The Empirical Evidencementioning
confidence: 67%
See 1 more Smart Citation
“…Using specification curve analysis (16,17), an exhaustive econometric approach, they observed, in contrast to previous findings on the selection of sports and risky play, that birth order had no substantive effect on risk taking, or indeed on the various personality dimensions examined. Recently, these results were supported in an Indonesian sample (9).…”
Section: The Empirical Evidencementioning
confidence: 67%
“…A recent study using data from three large national panel studies, including the German Socio-Economic Panel (SOEP), controlled for these methodological problems and found that birth order had no substantive effect on personality traits and only a negligible effect on intelligence (7). In parallel, the largest yet study of birth-order effects, which used a sample of 377,000 US high school students, found the same results (8), which were recently corroborated in a non-Western sample (9). For its authors, Damian and Roberts (10), Rohrer et al's (7) work has settled the debate: Birth order has no effect on personality.…”
Section: The Empirical Evidencementioning
confidence: 82%
“…This obligation causes them to stay single and focus on their career. Another reason is that higher birth order is related to higher educational attainment (Botzet, Rohrer and Arslan 2018), which reduces the likelihood of being single.…”
Section: Variable 2007 2017mentioning
confidence: 99%